Eosinophilia in Very Low Birth Weight Infants - Jui-Mei Yen; Chyi-Her Lin; Mei-Mei Yang; Shih-Ting Hou; Ai-Hsi Lin; Yuh-Jyh Lin (Pediatrics and Neonatology)
Eosinophilia is common in premature infants, though its clinical significance remains unknown. This study investigated the pattern of eosinophilia and related factors in very low birth-weight (VLBW) infants. Methods: The medical records of VLBW infants (birth body weight < 1500 g) admitted to the neonatal intensive care unit of a tertiary care center of Cheng Kung University Hospital between January 2005 and June 2007 were analyzed. Complete blood counts (CBC) with differential leukocyte counts were performed weekly. Eosinophilia was defined as an eosinophil count of more than 0.700 × 109/L. The possible related factors were analyzed. Results: A total of 142 infants were recruited into the study. Those who did not survive after the first 28 days and those with less than four available CBCs were excluded, leaving 107 infants and 828 CBC measurements. Overall, 19.0% of CBCs (157/828) indicated eosinophilia and 69.0% of all infants had at least one instance of eosinophilia during their hospital stay. Eosinophilia mainly occurred in the third week of life (27.1%), with an average peak eosinophil count of 0.520 × 109/L. There were 37.3% of patients with mild eosinophilia (0.700-0.999 × 109/L), 50.7% with moderate eosinophilia (1.000-2.999 × 109/L), and 12% with severe eosinophilia (≥3.000 × 109/L). The demographic data and perinatal characteristics of infants with and without eosinophilia were comparable. Medical treatments including mechanical ventilation, antibiotic administration, total parenteral nutrition, intravenous catheterization, transfusion, and body weight gains were similar between the two groups. The eosinophil counts in the first week of life were significantly higher in infants with bronchopulmonary dysplasia (p < 0.05). They were also greater in VLBW infants with sepsis at the first, the third, the fourth, the fifth and the seventh weeks (p < 0.05). Conclusion: Eosinophilia is common in VLBW infants and occurs mainly in the third week of life. Higher eosinophil counts were associated with sepsis and family history of atopic eczema. Bronchopulmonary dysplasia was associated with higher eosinophil counts in the first week of life.